Modern American communes a dictionary - Sutton, Robert P. 1940-2009 (Greenwood Press, 2005)
This reference source contains biographies and historical overviews of 20th-century communes and utopias in the United States and those individuals involved with them. Robert P. Sutton provides a comprehensive history of both religious and secular utopian communities
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Communautés - États-Unis - Histoire - 20e siècle - Répertoires; Utopies - États-Unis - Histoire - 20e siècle - Répertoires; Geschichte; Collective settlements -- United States -- History -- 20th century -- Directories; Utopias -- United States -- History -- 20th century -- Directories; Siedlungssoziologie; Kommune; USA; Wörterbuch